2005
DOI: 10.1177/1049732304272059
|View full text |Cite
|
Sign up to set email alerts
|

AIDS-Related Stigma and Social Interaction: Puerto Ricans Living With HIV/AIDS

Abstract: People living with HIV/AIDS are stigmatized. Although personal and social consequences of this stigmatization have been documented, research regarding its impact on social interactions is scarce. Latinos, and Puerto Ricans in particular, have voiced concern regarding AIDS stigma. The authors investigated the key role of social interaction in the process of stigmatization through in-depth, semistructured interviews in a sample of 30 Puerto Ricans living with HIV/AIDS. Participants reported instances in which AI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
91
0
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(98 citation statements)
references
References 24 publications
(23 reference statements)
3
91
0
4
Order By: Relevance
“…Therefore, HIV-infected people who fear from the disclosure of their status because of stigma and discrimination are willing to hide their status. They think disclosing their status may not only create a complicated and stressful situation, but also causes the person to lose family support and health care provision (19,20). Find-ings from a study conducted on HIV-positive people in South Africa indicated that 57% of the sample reported their status secretly, 73% had the feeling of guilt due to their positive status, and 43% had the feeling of shame (4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, HIV-infected people who fear from the disclosure of their status because of stigma and discrimination are willing to hide their status. They think disclosing their status may not only create a complicated and stressful situation, but also causes the person to lose family support and health care provision (19,20). Find-ings from a study conducted on HIV-positive people in South Africa indicated that 57% of the sample reported their status secretly, 73% had the feeling of guilt due to their positive status, and 43% had the feeling of shame (4).…”
Section: Introductionmentioning
confidence: 99%
“…The fear from stigma causes denial, secrecy, depression and shame. The disclosure of HIV status faces the person with the feelings of shame and selfsuspicion (19). Therefore, HIV-infected people who fear from the disclosure of their status because of stigma and discrimination are willing to hide their status.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies focused on the Norman 77 development of stigma scales for measuring felt stigma as well as stigma among health professionals in training (Jiménez et al, 2010;Varas-Diaz, and Neilands 2009;. Lastly, one study examined AIDS-related stigma and social interaction among PLWHA (Varas-Diaz et al, 2005). Findings from this study support the need for interventions to address AIDS stigma and its consequences.…”
Section: Previous Research Examining Hiv-related Stigma Toward Plwhamentioning
confidence: 63%
“…En este dominio se encontraron investigaciones con el menor puntaje como el estudio de Allen J et al (44±20), lo que podría explicarse por el estigma y la discriminación, ya que el VIH/sida generalmente se desarrolla en contextos donde prima la connotación moral y/o religiosa y al comunicar el diagnóstico se deteriora la interacción con los miembros de la familia, se presentan rupturas abruptas de la relación con los amigos, se afecta la relación con los compañeros de trabajo e incluso se presenta la pérdida del empleo, lo que deriva en abandono y alteración de la funcionalidad familiar y social de los sujetos infectados 38 .…”
Section: Figura 3 Análisis De La Cvrs Según Las Dimensiones Del Whoqounclassified